Diffusion coefficients in multiphase Ni80Cr20-Ti system - Wierzba B.; Serafin D.; Nowak W.J.; Wierzba P.; Ciećko A.; Mazurkow A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, the reactive diffusion in Ni80C20r–Ti ternary system is discussed at 1173K. The diffusion couple was prepared and annealed for 100 h. The two intermetallic phases and two two-phase zones occurred, namely: Ti2Ni, TiNi, TiNi+Cr, and TiNi3+Cr. Based on the experimental results (molar fractions, thicknesses of the intermetallic phases), the intrinsic diffusion coefficients of all components in each phase were numerically approximated. The Wagner method was used in the pure intermetallic phases. In the two phase zones the approximation was based on the generalized Darken and Wagner methods. The presented methods allowed for determination of the effective diffusion coefficients in each presented phase.